2020
DOI: 10.7759/cureus.8489
|View full text |Cite
|
Sign up to set email alerts
|

Acute Obstructive Choledocholithiasis: A Case of Elusive Gallstones on Imaging

Abstract: Acute choledocholithiasis results when stones form in the gallbladder and then pass into the common bile duct, where they may become lodged and cause obstruction. To our knowledge, very few cases are reported in which multiple imaging techniques had failed to detect the presence of gallstones, as per current literature review. We report a case of a 73-year-old woman with nausea, vomiting, and jaundice who was found to have choledocholithiasis with negative imaging on abdominal ultrasound (US), CT, and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some authors concluded that biochemical markers alone were insufficient to predict stones, and suggest that a combination of radiographic studies and biochemical markers should be used to aid in decision making. 10,11…”
Section: Resultsmentioning
confidence: 99%
“…Some authors concluded that biochemical markers alone were insufficient to predict stones, and suggest that a combination of radiographic studies and biochemical markers should be used to aid in decision making. 10,11…”
Section: Resultsmentioning
confidence: 99%